2014
DOI: 10.1557/mrs.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of developing rechargeable magnesium batteries

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
304
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(315 citation statements)
references
References 53 publications
(34 reference statements)
1
304
0
4
Order By: Relevance
“…In this regard batteries based on divalent magnesium (Mg) have received increasing attention. 6,[8][9][10][11][12][13][14][15] The theoretical volumetric capacity of a Mg anode, 3833 mAh/cm 3 , is nearly double that of monovalent Li, 2046 mAh/cm 3 . 8, 16-17 A Mg-based battery may also possess advantages in safety and cost compared to Li systems.…”
mentioning
confidence: 99%
“…In this regard batteries based on divalent magnesium (Mg) have received increasing attention. 6,[8][9][10][11][12][13][14][15] The theoretical volumetric capacity of a Mg anode, 3833 mAh/cm 3 , is nearly double that of monovalent Li, 2046 mAh/cm 3 . 8, 16-17 A Mg-based battery may also possess advantages in safety and cost compared to Li systems.…”
mentioning
confidence: 99%
“…[47] As a full inorganic electrolyte, the MACC electrolyte has drawn much attention in the community, and has been extensively studied in recent years. [48][49][50][51][52] − . [53] The oxidative stability of 2.5 V versus Mg on Pt electrode for this electrolyte is inferior to the reported MACC solution in a pure ethereal solvent and the ionic liquid possibly contributed to the high ionic conductivity of the electrolyte (8.5 mS/ cm).…”
Section: Combinations Of Magnesium Chloride With Aluminum-based Lewismentioning
confidence: 99%
“…[115,116] For these reasons, since the Mg rechargeable cell was proposed by Gregory et al [117] and the first prototype of a Mg ion cell was reported by Aurbach et al, [118] most research on Mg rechargeable cells has mainly focused on developing high capacity cathodes and appropriate organic electrolytes, which are strongly emphasized in the recent review articles. [115,116,119] In the historical development of Mg rechargeable cells, there were two significant breakthroughs; [116] (1) the report of solutions containing Mg organo-borate moieties that provide an environment for reversible Mg deposition/dissolution, even in the absence of highly reducing Grignard reagents, (2) (copyright is needed) [116] Since the DCC family of electrolytes was proposed, many types of cathodes have been tested such as transition metal disulfides [120] and Cheveral type cathodes in the DCC electrolytes. [118] could be achieved due to the fast insertion kinetics of Mg 2+ ions provided by its structure that has many vacant sites for Mg, a short diffusion distance between accommodation sites and easy charge compensation of the metallic Mo cluster during Mg diffusion.…”
Section: Magnesium Rechargeable Batteriesmentioning
confidence: 99%
“…Aurbach et al categorized Mg-cell electrolytes into four types in their recent review paper: [119] (1) Grignard-based electrolytes, (2) advanced Grignard-based electrolytes with high anodic stability, (3) non-Grignard based electrolytes, and (4) MgTFSI 2 -based electrolytes. The first electrolyte for Mg rechargeable cells was reported in the 1920s, which was composed of Grignard reagents (R-MgX, R = C 6 H 5 X = Br, Cl).…”
Section: Magnesium Rechargeable Batteriesmentioning
confidence: 99%